Magnetohydrodynamics stagnation point flow over a stretching or shrinking sheet in a porous medium with velocity slip and suction - Rosali, Haliza; Alias, Amir Azian (Universiti Putra Malaysia, 2024)
From previous studies, the current understanding is limited, and there is a lack of comprehensive research addressing the combined effects of slip, suction, porous medium, stretching/shrinking sheets, and magnetohydrodynamics on flow behaviour. Therefore, this study examines the magnetohydrodynamic stagnation point flow over a stretching or shrinking sheet in a porous medium in the presence of velocity slip and suction effects. By applying a suitable similarity transformation, a system of ordinary differential equations (ODEs) is obtained from the governing system of partial differential equations (PDEs). The resulting system, subjected to boundary conditions, is solved numerically using the bvp4c solver in MATLAB software. The governing parameters investigated in this study include velocity and temperature profiles, skin friction coefficients, and the local Nusselt number. The parameters considered are the magnetic parameter (M), slip parameter (A), permeability parameter (K), and suction parameter (S), in relation to the stretching or shrinking parameter (c). The results show that dual solutions exist for the shrinking sheet (c < 0), while a unique solution is obtained for the stretching sheet (c > 0). An increase in the magnetic parameter M, permeability parameter K, and suction parameter S leads to higher skin friction coefficients, whereas an increase in the slip parameter A reduces the skin friction coefficient. Additionally, increasing M, K, A, and S enhances the Nusselt number.